Yeast Glycogen Synthase Kinase-3 Pathway Inhibitors from an Organic Extract of Streptomyces sp. - Cheenpracha, Sarot; Hui, Zhang; Mar, Annie M. N.; Foss, Adam P.; Sek, Hin Foo; Ngit, Shin Lai; Jap, Meng Jee; Heng, Fong Seow; Coy, Choke Ho; Leng, Chee Chang (American Society of Pharmacognosy & American Chemical Society, 2009)
Investigation of a microbial fermentation organic extract of Streptomyces sp. H7667 led to the isolation of three new imides, 3-[(5E)-5-methyl-4-oxo-2-hydroxy-5-octenyl glutarimide (1), 2-amino-N-2′-(phenylacetyl)propanimide (5), and 2-amino-N-(2′-(cyclohex-2′′-enyl)acetyl)acetimide (6), and one new isoflavonoid glycoside, 6-O-methyl-7-O-Rrhamnopyranosyldaidzein (7), along with four known compounds. Their structures were elucidated by HRESIMS, 1H and 13C NMR, COSY, HMQC, HMBC, and NOESY spectra. Compounds 1-8 were evaluated for their inhibitory activities in the yeast glycogen synthase kinase-3 assay.